2020
DOI: 10.1021/acsomega.0c01270
|View full text |Cite
|
Sign up to set email alerts
|

Graphite/Graphene Composites from the Recovered Spent Zn/Carbon Primary Cell for the High-Performance Anode of Lithium-Ion Batteries

Abstract: Exploring electrochemically chapped graphite/graphene composites derived from the bulk carbon rod of the spent Zn/carbon primary cell is for the advanced high-capacity lithium-ion battery anode. It is found that the synthesized graphitic carbon has grain boundary defects with multilayered exfoliation. Such material exhibits an average specific capacity of 458 mA h g–1 at 0.2 C, which is higher than the theoretical specific capacity (372 mA h g–1) of graphite. The differential specific capacity calculations als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…As shown in Figure 6d, the specific capacity of the MoO 2 /C nanofiber membrane electrode decreased correspondingly with the current density increased during the continuous cycles. Even at a high current density of 2000 mA g −1 , the reversible specific capacity of the electrode was 432 mAh g −1 , which is still higher than the theoretical capacity of graphite (372 mAh g −1 ) [49], and when the current density dropped to 100 mA g −1 , the reversible specific capacity of the MoO 2 /C nanofiber membrane electrode also rose to a high level of 800 mAh g −1 and remained stable. This indicates that the MoO 2 /C nanofiber membrane electrode had excellent rate performance and stability performance, and that there was no memory effect on the electrode, reflecting the characteristics of LIBs [42].…”
Section: Electrochemical Propertiesmentioning
confidence: 77%
“…As shown in Figure 6d, the specific capacity of the MoO 2 /C nanofiber membrane electrode decreased correspondingly with the current density increased during the continuous cycles. Even at a high current density of 2000 mA g −1 , the reversible specific capacity of the electrode was 432 mAh g −1 , which is still higher than the theoretical capacity of graphite (372 mAh g −1 ) [49], and when the current density dropped to 100 mA g −1 , the reversible specific capacity of the MoO 2 /C nanofiber membrane electrode also rose to a high level of 800 mAh g −1 and remained stable. This indicates that the MoO 2 /C nanofiber membrane electrode had excellent rate performance and stability performance, and that there was no memory effect on the electrode, reflecting the characteristics of LIBs [42].…”
Section: Electrochemical Propertiesmentioning
confidence: 77%
“…Figure shows the N 2 adsorption–desorption isotherm and corresponding pore size distribution curves of rGO. BET isotherm follows type IV isotherms with a hysteresis loop, indicating the presence of mesopores, according to IUPAC classification. , Pore size distribution has been assessed by assuming slit pore shapes through hybrid nonlocal density functional theory (NLDFT) revealed that the pore diameter is in the range 2–17 nm, confirming the mesoporous structure of rGO. ,, …”
Section: Resultsmentioning
confidence: 97%
“…29,30 Pore size distribution has been assessed by assuming slit pore shapes through hybrid nonlocal density functional theory (NLDFT) revealed that the pore diameter is in the range 2−17 nm, confirming the mesoporous structure of rGO. 24,31,32 3.3. Electrical and Electrochemical Studies.…”
Section: Xps Studiesmentioning
confidence: 99%
“…[89] As Gr is the main source for production of graphene, recently, some studies have been investigating production of graphene from recycled Gr of EoL-LIBs, [90][91][92][93][94] or other batteries. [95,96] The applications have in common that the Gr of the EoL-LIBs has to be processed to graphene and freed from foreign substances via a common approach, typically the Hummers method. [90][91][92][93][94]97] For this purpose, typically, the battery was disassembled manually at the electrode level.…”
Section: Graphene Production From R-grmentioning
confidence: 99%
“…Next, deionized water and hydrogen peroxide were added, and, after filtration and drying, a subsequent sonication, washing, and centrifugation step was applied to the filtrated powders in order to produce the graphene to be used for further applications. [90][91][92][94][95][96][98][99][100] Some of the typical characterization methods and experimental steps used for the fabricated graphene from spent Gr are shown in Figure 9 and Table 4.…”
Section: Graphene Production From R-grmentioning
confidence: 99%